Rancang Bangun Aplikasi Dashboard Akademik SMA SHAFTA Surabaya - Sugesti Irawan; Erwin Sutomo; sri suhandiah (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
SMA SHAFTA is one of high school education  institution which is located at Jl. Lontar Citra Raya Surabaya. SMA SHAFTA Surabaya. Have an information System including the System of academic information. The lack of academic information have an impact on the educational process which will impact on the assessment or accreditation of the high school SHAFTA. Academic dashboard application is an application can help to monitor the academic activity foreach students. The application was made with SDLC method. The testing result shows that the application can give informations in visual form with their key performance indicators.